Strategi Pemasaran Untuk Meningkatkan Tingkat Hunian Kamar Pasca Pandemi Covid-19 Di Hotel Mercure Kuta Beach Bali - Febrianto, Stefanus Eka; Yuni, L.K. Herindiyah Kartika; Suryaningsih, Ida Ayu Anggreni (Universitas Triatma Mulya, 2023)
The emergence of COVID-19 in 2020 has shaken the world of the tourism industry, tourist attractions, places to stay, and existing culinary businesses. Many of these places have to close temporarily or permanently. The purpose of this study is to determine the marketing strategy for room occupancy rates at Mercure hotels after the COVID-19 pandemic that hit Indonesia, especially in Bali and to find out how effective the marketing strategy carried out by Mercure hotels. This research is a descriptive study using primary data obtained through interviews with actors related to the marketing strategy of room occupancy rates at Mercure Hotels after the COVID-19 pandemic and secondary data obtained from reports or records or information on websites, the internet or data from departments related to this thesis. The research results based on the marketing mix analysis show that the hotel continued to operate and hire employees during the pandemic. After the pandemic, the hotel normalized work shifts by implementing health protocols.